THE INFLUENCE OF TEACHER COMPETENCE AND TEACHER PERFORMANCE ON PRIMARY SCHOOL QUALITY - Murthofiah, Murthofiah; Nurkolis, Nurkolis; Sulianto, Joko (FORUM PAEDAGOGIK, 2024)
The purpose of this study was to determine the effect of teacher competence on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency. To determine the effect of teacher performance on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency. To determine the effect of teacher competence and teacher performance together on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency. The population in this study were elementary school class teachers in Ungaran Barat District, Semarang Regency, totaling 276 teachers from 25 schools. The sampling technique used in this study was the area proportional random sampling technique from a population of 276, 166 samples were obtained. The variables in this study consisted of independent variables, namely teacher competence and teacher performance, while the dependent variable was school quality. Data collection techniques using questionnaires. The data analysis technique used simple regression analysis and multiple regression. Before testing with regression analysis, the prerequisite test for data analysis was first used using the normality, linearity and multicollinearity tests with α = 0.05%). The findings of this study are as follows: there is a positive and significant influence of teacher competence on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency by 42.3%. There is a positive and significant influence of teacher performance on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency by 38.9%. There is a positive and significant influence together between teacher competence and teacher performance on the quality of Elementary Schools in Ungaran Barat District, Semarang Regency by 56.10%. The suggestion that can be conveyed is for the principal to provide encouragement and enthusiasm to his teachers to always improve their competence and performance by always being active to all teachers to become driving teachers and actively participating in the existing PMM, while for the program and financing of teacher competence improvement activities are included in ARKAS so that teacher competence and performance are getting better and have implications for school quality.